Power system relaying - Horowitz, Stanley H., 1925- (John Wiley & Sons Ltd, 2014)
"The previous three editions of Power System Relaying offer comprehensive and accessible coverage of the theory and fundamentals of relaying and have been widely adopted on university and industry courses worldwide. With the third edition, the authors have added new and detailed descriptions of power system phenomena such as stability, system-wide protection concepts and discussion of historic outages. Power System Relaying, 4th Edition continues its role as an outstanding textbook on power system protection for senior and graduate students in the field of electric power engineering and a reference book for practising relay engineers. Provides the student with an understanding of power system protection principles and an insight into the phenomena involved. Discusses in detail the emerging technologies of adaptive relaying, hidden failures, wide area measurement, global positioning satellites and the specific application of digital devices. Includes relay designs such as electromechanical, solid-state and digital relays to illustrate the advantages and disadvantages of each. Re-examines traditional equipment protection practices to include new concepts such as transmission line differential protection, load encroachment on distance relay characteristics, distributed generation systems, and techniques to improve protection system response to power system events. Analyzes system performance through oscillographs and alarms schemes. Features problems to be worked through at the end of each chapter. "--